A review on vehicle radiator using various coolants - Ihsan Naiman, Ibrahim; Norazlianie, Sazali; Ahmad Shahir, Jamaludin; D., Ramasamy; S. M., Soffie; Mohd Hafiz Dzarfan, Othman (Akademi Baru, 2019)
In a radiator, force convectional is the important thing that can be considered. The examples of convectional heat transfer fluids are nanofluid, water, glycerol, Ethylene Glycol and nanocellulose. These base fluids have been used widely in automotive radiators and these fluids recently have very low thermal conductivities. In advance, many researches have been done regarding to the study of enhancement of the convective heat transfer performance in nanoparticles. On the other hand, using nanofluids, due to the enhanced heat carrying capacity of the nanofluids; the pumping power required will also be reduced. All of these transfer fluids play an important role in many industrial sectors such as air-conditioning, transportation, microelectronics, power generation and chemical production.